Change request impacts in software maintenance - Kumar, Madapuri Rudra; Prasad, Kalli Srinivasa Nageswara; Rao, Annaluri Sreenivasa; Gunjan, Vinit Kumar (Boca Raton, FL : CRC Press, 2020)
"This book discusses Change Management Impact Analysis and how this method is used to analyze the risks and benefits of a change management initiative when it pertains to obtaining critical insight into how the change management program budget should be allotted. The process also offers useful indicators for what areas within the system should be monitored during the change management process. This book presents theoretical analysis of practical implications and surveys, along with analysis. It covers the functions aimed at identifying various stakeholders associated with the software such as requirement component, design component, and class component. The book talks about the interrelationship between the change and the effects on the rest of the system and dives deeper to include the critical role that the analysis places on the existing multiple functions such as estimating the development costs, the project overhead costs, cost for the modification of the system, and system strength or detecting errors in the system during the process. Case studies are also included to help researchers and practitioners to absorb the material presented. This book is useful to graduate students, researchers, academicians, institutions, and professionals that are interested in exploring the areas of Impact Analysis"--
OCLC-licensed vendor bibliographic record.
Keywords: Software maintenance -- Management; Computer software -- Management; TECHNOLOGY / Manufacturing; COMPUTERS / Programming / Software Development